Shear behaviour of vertical inter-module connection with bolts and shear keys for MSCs. (January 2023) - Shi, Feng-Wei; Ding, Yang; Zong, Liang; Chen, Yang; Wu, Ying
Abstract: Modular steel constructions (MSCs) are increasingly used in mid- to high-rise buildings because of their advantages in higher manufacturing quality, faster on-site installation speed, higher material use efficiency, lower life-cycle cost, as well as some other environment-friendly features. Shear tests of vertical inter-module connections with bolts and shear keys, which play a critical role in the lateral performance of MSCs, were carried out to investigate their shear load-carrying capacities and shear mechanical characteristics. Refined numerical models were established, calibrated against the test results and used to simulate the shear behaviour of vertical inter-module connections. The effects of friction coefficient and axial compression ratio on the shear behaviour were investigated. The connections were shown to exhibit excellent initial shear load-slip behaviour and shear load-carrying capacity under shear load. In terms of initial shear stiffness and slip resistance, the axial compression ratio and friction coefficient were shown to be the critical parameters, while the shear key and high-strength bolt dominated the ultimate shear resistances. Shear processes of vertical inter-module connections in different shear directions were almost consistent, which can be divided into the micro slipping stage, macro slipping stage, bearing stage and failure stage. Through geometrical parameters correlation analysis, a piecewise polynomial simplified shear load-deformation model was proposed for predicting the shear load-deformation relationship. The proposed model was shown to be capable of accurately capturing the shear behaviour of the connection, and is therefore recommended for use in engineering applications and future research on inter-module connections.